Delivering the Goods: Web OPACs and the Expanding Role of the Cataloger - Norm Medeiros (Issues in Science and Technology Librarianship)
The proliferation of information available on the Internet is staggering. Although library web sites offer a means of access to Internet resources, these lists often lack subject analysis, cross-referencing, and ultimately prove useless to those unaware of their presence. To that end, bibliographic records represented in web OPACs can describe Internet resources and link directly to them. Catalogers are experiencing a renaissance as the online catalog becomes both atlas and vehicle to Internet-based information.